2022
DOI: 10.1002/adfm.202107434
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a Soft Pressure Sensor in Terms of the Molecular Weight of the Ferroelectric‐Polymer Sensing Layer

Abstract: Tactile sensing is considered essential for effective object handling by robots. To this end, flexible smart materials are being extensively researched for application as soft pressure sensors. This paper proposes a soft pressure sensor featuring a ferroelectric-polymer sensing layer for dynamic pressure detection during robotic grasping operations. The solution-processed sensing layer is optimized in terms of the molecular weight of the ferroelectric polymer and the processing solvent. The proposed sensor exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…6 Organic polymer materials, such as polyvinylidene fluoride (PVDF) and its copolymer poly(vinylidene fluoride-trifluoro ethylene) (P(VDF-TrFE)), have become pioneering materials in the development of flexible electronic devices owing to their excellent piezoelectric properties, chemical stability, mechanical strength, and biocompatibility. [15][16][17][18] PVDF and P(VDF-TrFE) are easy to synthesize and combine with functional materials, which make them more appropriate for flexible sensing and energy harvesting domains. 16,17 It is reported that pure PVDF and P(VDF-TrFE) have the best d 33 of 30-40 pC N À1 compared to other polymers owing to the presence of a high b-content responsible for superior piezoelectric current generation.…”
Section: Venkata Sreenivas Pulimentioning
confidence: 99%
See 3 more Smart Citations
“…6 Organic polymer materials, such as polyvinylidene fluoride (PVDF) and its copolymer poly(vinylidene fluoride-trifluoro ethylene) (P(VDF-TrFE)), have become pioneering materials in the development of flexible electronic devices owing to their excellent piezoelectric properties, chemical stability, mechanical strength, and biocompatibility. [15][16][17][18] PVDF and P(VDF-TrFE) are easy to synthesize and combine with functional materials, which make them more appropriate for flexible sensing and energy harvesting domains. 16,17 It is reported that pure PVDF and P(VDF-TrFE) have the best d 33 of 30-40 pC N À1 compared to other polymers owing to the presence of a high b-content responsible for superior piezoelectric current generation.…”
Section: Venkata Sreenivas Pulimentioning
confidence: 99%
“…[15][16][17][18] PVDF and P(VDF-TrFE) are easy to synthesize and combine with functional materials, which make them more appropriate for flexible sensing and energy harvesting domains. 16,17 It is reported that pure PVDF and P(VDF-TrFE) have the best d 33 of 30-40 pC N À1 compared to other polymers owing to the presence of a high b-content responsible for superior piezoelectric current generation. 16 For instance, Lv et al, in 2022, developed a wireless sensor using a highly piezoelectric P(VDF-TrFE), whose d 33 is nearly 33.7 pC N À1 .…”
Section: Venkata Sreenivas Pulimentioning
confidence: 99%
See 2 more Smart Citations
“…Current advancements in state-of-the-art technologies have increased the demand for intelligent wearable electronic devices. Flexible pressure sensors are vital for physical-to-electrical signal conversions. These signal conversions play important roles in numerous fields including wearable devices, disease diagnostics, and intelligent robotics. However, some practical challenges remain including the compatibility of the pressure sensor with various objects, sensitivity of monitoring external force, linear detection range, and stability. The development of flexible electronic skins with high sensitivity, wide linear detection range, and excellent stability is of great significance and would facilitate their versatile practical applications.…”
Section: Introductionmentioning
confidence: 99%